Economic loss risk assessment for pressure variation on methanol production / Mohd Aizad Ahmad ... [et al.] - Ahmad, Mohd Aizat; Abdul Rashid, Zulkifli; Ahmad Fuad, Mohd Fazril Irfan; Jamaludin, Iqbal; Alias, Azil Bahari (Universiti Teknologi MARA Shah Alam, 2022)
The purpose of this paper is to assess the economic loss risk by combining economic loss and frequencies of events per year on methanol production due to piping and reactor incidents. This study assessed the amount of economic loss caused by fatalities-injuries, equipment damage, business disruption, and emergency services of toxicity, thermal radiation, and overpressure events on various pressure reactor conditions for a proposed methanol plant in Manjung, Perak, Malaysia. These case studies compare 7 plants comprising the Conventional Plant using a pressure of 76 bar and reactor size of 42 m3 and 6 modified plants using downsize reactor of 7.6 m3 and having pressure conditions of 76, 100, 200, 300, 400, and 500 bar, respectively. The methanol reactor has hazardous chemicals of hydrogen, carbon dioxide, carbon monoxide, and methanol. The number of fatalities-injuries and equipment damage loss was estimated using consequence analysis multiplied by the monetary value of people and equipment. Business disruption loss is calculated using plant outage time and Industry Value Added per employee while emergency service loss is two percent of overall loss. Results proved that the Conventional Plant has a total economic loss risk of RM 766.5k annually while all modified plants have safety improvements between 64% to 89% compared to the Conventional Plant.